1986
DOI: 10.1172/jci112516
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that serum calcium oxalate supersaturation is a consequence of oxalate retention in patients with chronic renal failure.

Abstract: Serum oxalate rises in uremia because of decreased renal clearance, and crystals ofcalcium oxalate occur in the tissues of uremic patients. Crystal formation suggests that either uremic serum is supersaturated with calcium oxalate, or local oxalate production or accumulation causes regional supersaturation. To test the first alternative, we ultrafiltered uremic serum and measured supersaturation with two different methods previously used to study supersaturation in urine. First, the relative saturation ratio (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 52 publications
4
45
1
Order By: Relevance
“…This indicated that prolonged (6-8 h) dialysis as recommended during the pretransplant period may not be required after liver transplantation in PH1. We also observed that at 24 h after each HD treatment the serum oxalate level was in the range of 24-34 Ìmol/l, which was far below the reported pre-HD level of 170 B (SD) 21 Ìmol/l in oxalosis-related ESRD patients [22] and also below the supersaturation level of 50 Ìmol/l reported by Worcester et al [13]. Thus, the frequency of HD was reduced to three times per week.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…This indicated that prolonged (6-8 h) dialysis as recommended during the pretransplant period may not be required after liver transplantation in PH1. We also observed that at 24 h after each HD treatment the serum oxalate level was in the range of 24-34 Ìmol/l, which was far below the reported pre-HD level of 170 B (SD) 21 Ìmol/l in oxalosis-related ESRD patients [22] and also below the supersaturation level of 50 Ìmol/l reported by Worcester et al [13]. Thus, the frequency of HD was reduced to three times per week.…”
Section: Discussioncontrasting
confidence: 51%
“…While HD is more efficient than CAPD in removing oxalate, in order to achieve a negative or zero oxalate balance in oxalosis-related ESRD patients, one needs to undergo at least 6-8 h of daily HD [12]. Nevertheless, in an elegant study on 11 oxalosis-unrelated ESRD patients, it was shown that routine HD reduced the supersaturated serum to an unsaturated state (pre-HD serum oxalate level 89 B 8 Ìmol/l, post-HD 31 B 4 Ìmol/l, normal serum level 10 B 3 Ìmol/l; mean B SD) [13].…”
Section: Discussionmentioning
confidence: 99%
“…Supersaturation of plasma with respect to calcium and oxalate is a risk factor for calcium oxalate deposition in tissues. [42][43][44] The risk becomes significant when plasma oxalate concentrations exceed 28 to 50 mol/L. This degree of hyperoxalemia develops at renal clearances of 24 to 34 mL/min/1.73 m 2 in patients with PH and 8 to 11 mL/min/1.73 m 2 in patients with other causes of renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…This degree of hyperoxalemia develops at renal clearances of 24 to 34 mL/min/1.73 m 2 in patients with PH and 8 to 11 mL/min/1.73 m 2 in patients with other causes of renal disease. 42,45 Oxalate dynamic studies suggest that an increase in the oxalate metabolic pool size and, by inference, tissue oxalate accumulation may occur earlier in PH when renal clearance is 40 to 60 mL/min/1.73 m 2 . 3,46 In agreement with these observations, early introduction of transplantation or dialysis is recommended for plasma oxalate concentrations greater than 30 mol/L and/or glomerular filtration rates of 25 to 30 mL/min/ 1.73 m 2 or less.…”
Section: Discussionmentioning
confidence: 99%
“…Deposition of calcium oxalate microcrystal in soft tissues has been observed in primary hyperoxaluria, chronic renal failure, and certain small bowel diseases (2,3,20). Although pathologic conditions may arise occasionally when the body fluid is supersaturated with calcium oxalate, its precipitation is normally inhibited by a number of low-molecular weight inhibitors and macromolecular inhibitors (3).…”
Section: Introductionmentioning
confidence: 99%